Promises and image concerns - Miriam Schütte; Carmen Thoma (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
According to several psychological and economic studies, non-binding communication can be an effective tool to increase trust and enhance cooperation. This paper focuses on reasons why people stick to a given promise and analyzes to what extent image concerns of being perceived as a promise breaker play a role. In a controlled laboratory experiment, we vary the ex post observability of the promising party's action in order to test for social image concerns. We observe that slightly more promises are kept if the action is revealed than if it is not, yet the difference is not significant. However, a variation in the selection of pre-defined messages across treatments delivers another interesting finding. While most of the promises are kept, statements of intent tend to be broken.
Keywords: C70; C91; D03; D82; 330; Promises; communication; social image concerns; guilt; shame; behavioral economics; experiment